Synthesis and Antimalarial Activity of 2-Phenyl-1,10-Phenanthroline Derivative Compounds - Hadanu, Ruslin; Mustofa, Mustofa; Nazudin, Nazudin (Jurnal Natur Indonesia, 2013)
To develop new potential antimalarial drugs of 2-phenyl-1,10-phenanthroline 5 derivatives from 8-aminoquinoline as startingmaterial were synthesized in good yields. The synthesis of 2-phenyl-1,10-phenanthroline 5 derivatives compoundswith 8-aminoquinoline 4 as starting material through three steps has been carried out. The first step of reactions is aldolcondensation of benzaldehyde 1 with acetaldehyde 2. The result of reactions is cinnamaldehyde 3 (92.14%) in the form ofyellow solid. The second step of reactions was synthesized of 2-phenyl-1,10-phenanthroline 5 (brown solid, 54.63%)through cyclization of 8-aminoquinoline 4 with cinnamaldehyde 3 compound. The third step of reactions is methylation andethylation of 2-phenyl-1,10-phenanthroline using dimethyl sulphate (DMS) and diethyl sulphate (DES) reagents that it wasrefluxed for 17 and 19 h, respectively. The results of reactions are (1)-N-methyl-9-phenyl-1,10-phenanthrolinium sulphate 6and (1)-N-ethyl-9-phenyl-1,10-phenanthrolinium sulphate 7 in yield from 90.62% and 89.70%, respectively. The results oftesting in vitro antiplasmodial activity at chloroquine-resistant Plasmodium falciparum FCR3 strain to 2-phenyl-1,10-phenanthroline 5 derivatives obtained that (1)-N-ethyl-9-phenyl-1,10-phenanthrolinium sulphate 7 compound has higherantimalarial activity (IC 50 :0.13 ± 0.02 μM) than antimalarial activity of (1)-N-methyl-9-phenyl-1,10-phenanthrolinium sulphate6 compound (IC 50 :0.25 ± 0.01 μM) and 2-phenyl-1,10-phenanthroline 5 compound (IC 50 :2.45 ± 0.09 μM). While, the resultsof testing in vitro antiplasmodial activity at chloroquine-resistant Plasmodium falciparum D10 strain to 2-phenyl-1,10-phenanthroline 5 derivatives obtained that (1)-N-methyl-9-phenyl-1,10-phenanthrolinium sulphate 6 compound has higherantimalarial activity (IC 50 :0.10± 0.04 μM) than antimalarial activity of (1)-N-ethyl-9-phenyl-1,10-phenanthrolinium sulphate7 (IC 50 :0.18 ± 0.01 μM) and 2-phenyl-1,10-phenanthroline 5 compound (IC 50 :0.55 ± 0.07 μM).